Analisis Hukum tentang Tanggung Jawab Produsen Skincare yang Mengakibatkan Kerugian kepada Konsumen Menurut Undang-Undang Nomor 8 Tahun 1999 - Iwan Setyawan; Shella; Emia Ulina Tarigan (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2026)
The purpose of this study is to analyze the legal liability of skincare producers toward consumers under Law Number 8 of 1999 concerning Consumer Protection (UUPK) and to examine the judicial considerations in the Supreme Court Decision Number 1779 K/Pdt/2014. The research method employs a normative juridical legal research with a descriptive-analytical approach through a literature study of primary and secondary legal materials. The results indicate that skincare producers are obligated to guarantee product safety and provide compensation for consumer losses through the principle of strict liability. However, the Supreme Court Decision Number 1779 K/Pdt/2014 annulled the compensation on the grounds that the plaintiff was a promotional participant and not an end-consumer. The study concludes that there is a vacuum of substantive legal protection for non-transactional cosmetic product users (promotional participants/models) within Indonesian jurisprudence, thereby requiring an expanded interpretation of the definition of end-consumer to uphold the principle of legal justice. Keywords: Consumer Protection, Jurisprudence, Skincare, Strict Liability.